Singing the Night: Lullabies as Reflexive Practice in Music and Peacebuilding - Levesque, Lauren (Ethnologies, 2022)
This paper explores singing lullabies as a practice that opens spaces to reflect on ‘night’ as a sonic and sensory experience with implications for research in music and peacebuilding. Using arts-based and autoethnographic approaches, I ask: Can singing lullabies (Juvancic 2010) open a space to examine how sounding at night shapes a researcher’s ‘peace’ imaginary? This question aims to expand understandings of the ‘self’ as a site of an “aesthetics of resistance” (Möller 2020), or the notion that individual reflection and action sustain social engagement in music and peacebuilding scholarship. These understandings can contribute to interdisciplinary conversations on self-reflexivity and performance as ethnographic access points to peace imaginaries in Night Studies.